Implementasi Tata Kelola Perusahaan Untuk Mereduksi Manajemen Laba - Lusi Oktaviana; Rohmad Suryadi; Dewi Purnasari; Fitri Handayani (Economics and Digital Business Review, 2025)
The purpose of this study was to find outempirical evidence about the effect of managerial ownership, institutional ownership, public ownership, board of commissioners, independent board of commissioners, executive compensation on earnings management. Samples in the study were 106 manufacturing companies that had been selected by purposive sampling method. The analysis method uses multiple linear regression analysis techniques, proving that managerial ownership, institutional ownership, executive compensation does not effect earnings management. Public ownership, independent board of commissioners has negative effect earnings management and board of commissioners has positive effect earnings management.